Intraspecific functional differentiation suggests local adaptation to long‐term climate change in a calcareous grassland. (28th October 2013) - Ravenscroft, Catherine H.; Fridley, Jason D.; Grime, J. Philip; Cornelissen, Hans
Summary Populations of the common perennial herb Plantago lanceolata L. have been exposed to nearly two decades of summer drought at the Buxton Climate Change Experiment (BCCIL), a controlled manipulation of climate factors in a species‐rich limestone grassland in northern England. We used a common garden approach to test for evidence of selection for different suites of functional traits in P. lanceolata populations exposed to chronic summer drought and across a soil depth gradient. The main axis of functional variation reflected a trade‐off between reproductive and vegetative allocation, consistent with drought avoidance and competitive strategies, respectively. Avoidance strategies were more prominent in droughted populations, whereas competitive strategies were more prominent in populations from control treatments. Treatment differences were more pronounced in shallower soils. Deeper soils in both control and drought treatments promoted functional differentiation associated with competitive strategies, suggesting that selective pressures imposed by different climate treatments are modified by fine‐scale edaphic heterogeneity. Synthesis. Results suggest that population‐level shifts can be a mechanism of resistance to local climate‐induced extinction. Trait differentiation with respect to fine‐scale variation in soil depth suggests that edaphic heterogeneity fosters high local genetic diversity, which provides a range of local phenotypes upon which drought‐based selection may act.